2022
DOI: 10.1002/advs.202204715
|View full text |Cite
|
Sign up to set email alerts
|

High Electrochemiluminescence from Ru(bpy)32+ Embedded Metal–Organic Frameworks to Visualize Single Molecule Movement at the Cellular Membrane

Abstract: Direct imaging of single‐molecule and its movement is of fundamental importance in biology, but challenging. Herein, aided by the nanoconfinement effect and resultant high reaction activity within metal–organic frameworks (MOFs), the designed Ru(bpy)32+ embedded MOF complex (RuMOFs) exhibits bright electrochemiluminescence (ECL) emission permitting high‐quality imaging of ECL events at single molecule level. By labeling individual proteins of living cells with single RuMOFs, the distribution of membrane tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…This protein is widely expressed on the surface of cells and related to adhesion and migration of tumor cells (Figure 3A). [19] With the assistant of single molecule fluorescence imaging according to our previous report, [12] it is confirmed that individual SNECL spot can represent a single protein molecule (Figure S19). Figure 3B-D display single proteins on the surface of single MCF-7 cell offering distinct positions on the cell membrane which can be supported by comparative fluorescent imaging (Figure S20).…”
supporting
confidence: 60%
“…This protein is widely expressed on the surface of cells and related to adhesion and migration of tumor cells (Figure 3A). [19] With the assistant of single molecule fluorescence imaging according to our previous report, [12] it is confirmed that individual SNECL spot can represent a single protein molecule (Figure S19). Figure 3B-D display single proteins on the surface of single MCF-7 cell offering distinct positions on the cell membrane which can be supported by comparative fluorescent imaging (Figure S20).…”
supporting
confidence: 60%
“…, which has always been ignored in describing its ECL mechanism. 11,12 With the progress of weak optical signal detection, singleparticle 13 or even single-molecule 14 ECL imaging has become possible. These developed micro-imaging approaches can spatially separate different objects to provide far richer information than conventional ECL detection techniques.…”
Section: +mentioning
confidence: 99%
“…Two assumptions were given to describe this mechanism: (1) TPrA +• and TPrA • are formed on the electrode by electro-oxidation of TPrA and subsequent deprotonation, which diffuse into silica nanopores to reduce the dopant Ru­(bpy) 3 2+ and oxidize Ru­(bpy) 3 + , respectively, to produce Ru­(bpy) 3 2+ * and (2) Ru­(bpy) 3 2+ is directly oxidized through electron hopping and then reduced by TPrA • to produce Ru­(bpy) 3 2+ *. , To eliminate the interference of leaked Ru­(bpy) 3 2+ in interpreting the ECL process, Ru­(bpy) 3 2+ was covalently doped with silica nanoparticles (SNs) . However, the widely used RDSN is usually prepared by non-covalent doping; therefore, it is necessary to elucidate the mechanism in the presence of free Ru­(bpy) 3 2+ , which has always been ignored in describing its ECL mechanism. , …”
Section: Introductionmentioning
confidence: 99%
“…The successful visualization of a single protein at the electrode surface and cellular membrane indicated that the local surface confinement effect enabled spatially resolved imaging of single proteins, which opened up a new field in the biological application using ECL imaging. Subsequently, inspired by the nanoconfinement effect and high reactivity in the metal organic framework (MOF), Li et al designed the Ru(bpy) 3 2+ -embedded MOFs (RuMOFs) as ECL nanoemitters [ 118 ]. The unique multipole confined space in RuMOFs facilitates the electron/proton transfer and improves the accumulation of intermediate radicals, which permit high-quality imaging of individual ECL events and a stable ECL emission up to 1 h. By labeling individual proteins of living cells with single RuMOFs, this nanosystem achieves real-time ECL monitoring and dynamic mapping of protein molecules, and effectively differentiates the heterogeneity of movement direction and velocity among protein individuals in different regions.…”
Section: Ultrasensitive Bioanalysis By Different Ospi Techniquesmentioning
confidence: 99%